2016
DOI: 10.1155/2016/2587094
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, Pharmacogenetic, and Other Factors Influencing CNS Penetration of Antiretrovirals

Abstract: Neurological complications associated with the human immunodeficiency virus (HIV) are a matter of great concern. While antiretroviral (ARV) drugs are the cornerstone of HIV treatment and typically produce neurological benefit, some ARV drugs have limited CNS penetration while others have been associated with neurotoxicity. CNS penetration is a function of several factors including sieving role of blood-brain and blood-CSF barriers and activity of innate drug transporters. Other factors are related to pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 157 publications
0
30
0
Order By: Relevance
“…Inflammation at the blood-CSF barrier or the CSF-brain barrier could lead to altered drug distribution via opening of tight junctions, altered pH changing drug ionization, and downregulation of efflux transporters. 5 The effect of meningitis coinfection on antiretroviral CNS penetration has not previously been quantified.…”
Section: Antiretroviral Brain and Csf Concentrationsmentioning
confidence: 99%
“…Inflammation at the blood-CSF barrier or the CSF-brain barrier could lead to altered drug distribution via opening of tight junctions, altered pH changing drug ionization, and downregulation of efflux transporters. 5 The effect of meningitis coinfection on antiretroviral CNS penetration has not previously been quantified.…”
Section: Antiretroviral Brain and Csf Concentrationsmentioning
confidence: 99%
“…23 Appropriate use of ARVs allows for successful systemic suppression of peripheral viral load; however, eradicating HIV in the brain remains a challenge partly due to limited penetration of several ARVs. 24 Inadequate ARV concentrations in the brain may allow continuous HIV-1 replication and subsequent emergence of drug-resistant viral strains. 25 Additionally, studies have demonstrated that HIV-1-targeted brain cells such as microglia have ARV concentrations that are suboptimal to achieve efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of the CNS is characterized by the presence of multi-nucleated giant cells, reactive astrocytes, and white matter abnormalities. CNS infection remains a major obstacle to complete eradication of HIV in infected individuals, since many antiretrovirals cannot easily penetrate the blood-brain barrier, and are therefore less effective in eliminating infected cells (Nwogu et al , 2016). …”
Section: Introductionmentioning
confidence: 99%